Role of Microenvironment on the Fate of Disseminating Cancer Stem Cells - Ingangi, Vincenzo; Minopoli, Michele; Ragone, Concetta; Motti, Maria Letizia; Carriero, Maria Vincenza (Frontiers in Oncology, 2019)
Disseminating Cancer Stem Cells (CSCs) initiate growth in specific niches of the host tissues, the cellular and molecular components of which sustain signaling pathways that support their survival, self-renewal, dormancy and reactivation. In the metastatic niche, tumor cells may enter in a dormant state to survive and, consequently, the metastasis can remain latent for years. Despite the clinical importance of metastatic latency, little is known about what induces CSCs to enter a dormant state and what allows them to remain viable for years in this state. CSCs exhibit genetic, epigenetic and cellular adaptations that confer resistance to classical therapeutic approaches. The identification of potential CSC targets is complicated by the fact that CSCs may arise as a consequence of their relationship with the local microenvironment into the metastatic niches. Indeed, microenvironment modulates the capability of CSCs to evade the innate immune response and survive. Some new therapeutic options that include drugs targeting microenvironment components are achieving encouraging results in reducing the number of CSCs in tumors and/or overcoming their resistance in preclinical studies. This review will focus on specific CSC features with an emphasis on the role of tumor microenvironment in supporting metastatic dissemination of CSCs. In addition, it sheds light on potential microenvironment-targeted therapies aimed to counteract seeding and survival of CSCs in the metastatic niche.